2021
DOI: 10.21203/rs.3.rs-689210/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction and Detection of COVID-19 from Chest X-Rays using Transfer Learning based Deep Convolutional Neural Networks

Abstract: With the ongoing outbreak of the COVID-19 global pandemic, the research community still struggles to develop early and reliable prediction and detection mechanisms for this infectious disease. The commonly used RT-PCR test is not readily available in areas with limited testing facilities, and it lags in performance and timeliness. This paper proposes a deep transfer learning-based approach to predict and detect COVID-19 from digital chest radiographs. In this study, three pre-trained convolutional neural netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Subsequently, Naive Bayes classifier can predict the presence of TB on chest x-rays. These features provide better accuracy and specificity values than previously existing methods proposed by Alfadhli et al, 7 Islam et al, 17 and Hwang et al 18 when tested on the Shenzhen dataset. 25 In this research article, a balanced training model is developed using the optimal feature vector of dimension 12.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Subsequently, Naive Bayes classifier can predict the presence of TB on chest x-rays. These features provide better accuracy and specificity values than previously existing methods proposed by Alfadhli et al, 7 Islam et al, 17 and Hwang et al 18 when tested on the Shenzhen dataset. 25 In this research article, a balanced training model is developed using the optimal feature vector of dimension 12.…”
Section: Discussionmentioning
confidence: 77%
“…On comparison, the proposed algorithm has achieved better AUC and specificity than all the earlier existing algorithms proposed by Islam et al, 17 Stefan Jaeger et al, 12 Santosh et al 19 However, Stefan Jaeger et al 12 has reported better sensitivity than the proposed method due to better quality images and manual optimization techniques. In comparison, the proposed work is verified on…”
Section: Comparison With Existing Algorithmsmentioning
confidence: 77%
See 1 more Smart Citation
“…Techniques for detecting objects have considerably advanced since convolutional neural networks (CNNs) were introduced and are being used in enormous applications and fields like pedestrian detection [17], healthcare [18], and virtual assistants [19]. The ability to recognize objects in pictures and videos is one of the core challenges in computer vision, and it is connected to a wide range of applications, such as face recognition [20], self-driving cars [21], traffic and vehicle detection [22], natural language processing [23], agriculture [24], medical image analysis [25,26] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al. employed an ensemble of several models, including Alexnet, Resnet, and VGG 20 . The final result outperformed the use of classifiers for detecting cardiomegaly and tuberculosis.…”
Section: Introductionmentioning
confidence: 99%